2014
DOI: 10.1152/ajpregu.00116.2014
|View full text |Cite
|
Sign up to set email alerts
|

Leucine acts in the brain to suppress food intake but does not function as a physiological signal of low dietary protein

Abstract: ular injections of leucine are sufficient to suppress food intake, but it remains unclear whether brain leucine signaling represents a physiological signal of protein balance. We tested whether variations in dietary and circulating levels of leucine, or all three branched-chain amino acids (BCAAs), contribute to the detection of reduced dietary protein. Of the essential amino acids (EAAs) tested, only intracerebroventricular injection of leucine (10 g) was sufficient to suppress food intake. Isocaloric low-(9%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 45 publications
6
54
0
Order By: Relevance
“…Our previous work indicated that WT mice and rats exhibit significant increases in food intake when exposed to LP diet for 2 weeks (Laeger et al, 2014a; Laeger et al, 2014b; Morrison et al, 2007), and here this hyperphagic response extended to the entire 27 week experiment (Figure 1H). The increase in food intake was accompanied by a persistent increase in EE, as demonstrated by the increase in EE in WT-LP mice after 11 weeks on diet (Figure 1G and S2), and by the fact that the LP-induced hyperphagia did not produce weight gain.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Our previous work indicated that WT mice and rats exhibit significant increases in food intake when exposed to LP diet for 2 weeks (Laeger et al, 2014a; Laeger et al, 2014b; Morrison et al, 2007), and here this hyperphagic response extended to the entire 27 week experiment (Figure 1H). The increase in food intake was accompanied by a persistent increase in EE, as demonstrated by the increase in EE in WT-LP mice after 11 weeks on diet (Figure 1G and S2), and by the fact that the LP-induced hyperphagia did not produce weight gain.…”
Section: Resultssupporting
confidence: 63%
“…Dietary protein restriction is known to increase both food intake and energy expenditure (Gosby et al, 2014; Hasek et al, 2010; Laeger et al, 2014a; Laeger et al, 2014b; Morrison et al, 2007; Rothwell and Stock, 1987; Rothwell et al, 1983; Simpson and Raubenheimer, 1997, 2005; White et al, 2000). We observe similar effects in the current data, and demonstrate that these changes are persistent over the entire 6 month experiment.…”
Section: Discussionmentioning
confidence: 99%
“…In mice placed on a Low AA diet, this may be explained in part by an FGF21-mediated increase in energy expenditure (Laeger et al, 2014a), but mice eating a diet specifically reduced in the BCAAs do not have increased FGF21 or increased energy expenditure; the mechanism for this remains to be determined. Interestingly, a recent study in Sprague-Dawley rats determined that diets with reduced dietary BCAAs do not stimulate hyperphagia (Laeger et al, 2014b); whether this reflects differences between mice and rats, or experimental differences in the length of diet feeding and the degree of BCAA restriction remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, several groups confirmed that administration of physiologically relevant amounts of leucine into the 3rd ventricle or discrete brain nutrient-sensing regions of fasted rodents reduces energy intake during the subsequent refeeding period (26, 8688). This anorectic response is not produced by other branched-chain amino acids or any aromatic amino acids (26, 87), is not accompanied by the development of conditioned taste aversion (26, 86), persists for 24 h, and produces a significant decrease in body weight gain (26, 86), as summarized in Table 1. Brain leucine levels are increased following a meal, and brain leucine administration reduces food intake, suggesting that brain amino acid levels may constitute a signal of energy and/or protein availability detected by brain nutrient-sensing regions that modulate homeostatic feeding-regulatory circuits.…”
Section: Central Sensing Of Amino Acid Abundance and The Control Of Fmentioning
confidence: 97%
“…In contrast, marginally low-protein diets (LP, 8–10% of energy as protein in rats) with balanced EAA profiles induce a hyperphagic response restoring nitrogen and EAA intakes which, together with various metabolic adaptions, are sufficient to enable growth (87, 91, 104108). Conversely, high-protein diets (HP, 20–70% of energy as protein) produce a sustained decrease in energy intake that is not caused by taste aversion even at very high-protein levels (109, 110).…”
Section: Diets With Varying Protein Content: the Protein Leverage Hypmentioning
confidence: 99%